2007
DOI: 10.1021/jp072917r
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Calculation of pKa for Cocaine, Nicotine, Neurotransmitters, and Anilines in Aqueous Solution

Abstract: The absolute pK a values of 24 representative amine compounds, including cocaine, nicotine, 10 neurotransmitters, and 12 anilines, in aqueous solution were calculated by performing first-principles electronic structure calculations that account for the solvent effects using four different solvation models, i.e. the surface and volume polarization for electrostatic interaction (SVPE) model, the standard polarizable continuum model (PCM), the integral equation formalism for the polarizable continuum model (IEFPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 125 publications
1
61
0
Order By: Relevance
“…4A). Although these deficits were evident at pH 7.4 of the extracellular nicotine solution, they were much more prominent at pH 9.0 when the alkaloid is largely uncharged (pK a 8.02; Lu, Chen, Zhan, 2007) and, thus, well membrane-permeable. This is most likely due to the fact that both TRP receptor-channels have their binding sites for most agonists at the intracellular site of the transmembrane proteins (Vriens et al, 2009).…”
Section: Resultsmentioning
confidence: 95%
“…4A). Although these deficits were evident at pH 7.4 of the extracellular nicotine solution, they were much more prominent at pH 9.0 when the alkaloid is largely uncharged (pK a 8.02; Lu, Chen, Zhan, 2007) and, thus, well membrane-permeable. This is most likely due to the fact that both TRP receptor-channels have their binding sites for most agonists at the intracellular site of the transmembrane proteins (Vriens et al, 2009).…”
Section: Resultsmentioning
confidence: 95%
“…Accordingly, many researchers are tending to calculation of pKa values using theoretical and computational approaches. 21,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Recently quantum chemical calculations, using thermodynamical parameters such as Gibbs free energy, have reported good correlations between calculated and experimental acidities of a wide range of organic and inorganic acids. 18,[42][43][44][45][46][47][48][49][50] For example, gas phase and solution phase acidities of some organic compounds investigated by Namazian et al and Kheirjou et al reported good correlation between ab initio calculations of pKa values with the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Of the different quantum chemical methodologies available for the computation of pK a values the dielectric continuum solvation methods (DCSMs 9 ) have become quite popular in the recent years [10][11][12][13][14][15][16][17] since they are able to describe accurately long range electrostatic interactions of solutes at moderate computational cost in the context of quantum chemical programs. Despite the well-known deficiencies of DCSM methods, (i.e.…”
Section: Introductionmentioning
confidence: 99%